2004
DOI: 10.24200/jams.vol9iss1pp9-16
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics of Two Cichlids, Oreochromis aureus and Tilapia zilIi, from Wadi EI-Raiyan Lakes, Egypt

Abstract: Age, growth, mortality, relative yield-per-recruit and relative biomass-per-recruit of Oreochromis aureus and Tilapia zilli collected from Wadi EI-Raiyan lakes during the period from August 2000 until July 2001 have been estimated. Age was determined from scale readings and the results showed that the maximum life spans of O. aureus and T. zilli were three and four years, respectively. The von Bertalanffy growth equations were L1= 27.15 (l-e'0.56(t+0.32) for 0. aureus and L1= 33.5 (l-e -0.49(t+0.15) for T. zil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
25
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 4 publications
8
25
4
Order By: Relevance
“…The size of O. aureus found in the present study (6.6 to 22.9 cm) was similar those found by [22]in Wadi El-Raiyan Lakes, Egypt (8.0-23.9 cm), [24] in Rosetta branch of the Nile River, Egypt (10.5-24.5 cm), [31]in the Tigris River south of Baghdad, Iraq (3.5-27.9 cm), and [46]in the Shatt Al-Arab River, Basrah, Iraq (10-21.5 cm). However, the size of the species in the present study was lower than those reported from some other waters, such as 10.6-39.8 cm in the Benito Juárez dam, Mexico [47], 20.5-40.9 cm in El Infiernillo Reservoir, Mexico [23], and 13.9-53.8 cm in the Aguamilpa Reservoir, Mexico [25], This may be related to differences among fishing gear used, and to different of ecological condition of these habitats.…”
Section: Discussionsupporting
confidence: 92%
“…The size of O. aureus found in the present study (6.6 to 22.9 cm) was similar those found by [22]in Wadi El-Raiyan Lakes, Egypt (8.0-23.9 cm), [24] in Rosetta branch of the Nile River, Egypt (10.5-24.5 cm), [31]in the Tigris River south of Baghdad, Iraq (3.5-27.9 cm), and [46]in the Shatt Al-Arab River, Basrah, Iraq (10-21.5 cm). However, the size of the species in the present study was lower than those reported from some other waters, such as 10.6-39.8 cm in the Benito Juárez dam, Mexico [47], 20.5-40.9 cm in El Infiernillo Reservoir, Mexico [23], and 13.9-53.8 cm in the Aguamilpa Reservoir, Mexico [25], This may be related to differences among fishing gear used, and to different of ecological condition of these habitats.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the mean condition factor of Atherina boyeri in Lake Iznik, Turky, ranged from 0.41 to 0.80 (Ozeren, 2009), and from 0.49 to 0.60 in Hirfanli Reservoir in Turkey (Gencoglu and Ekmekçi, 2016). Many studies had been conducted to the length-weight relationship and condition factor of tilapia species in the Egyptian waters; in the River Nile (Tharwat, 1995;El-Kasheif, 2003;Mazrouh, 2008, Authman et al, 2009;Hassan & El-Kasheif, 2013;El-Bokhty & El-Far, 2014), in Lake Manzala ( Bayoumi & Khalil, 1988;Soliman et al, 1998;Shalloof, 1991;Bakhoum and Abdallah, 2002;El-Bokhty, 2006 andFarouk, 2009 ), in Lake Nasser (Latif & Khallaf, 1987;Agaypi, 1992;Mekkawy et al, 1994;Shenouda et al, 1995 andKhalifa et al, 2000 ), in Abu-Zabal Lakes (Ibrahim et al, 2008 andEl-Far, 2009), in Lake Qarun (Shalloof, 2009), in Wadi El-Rayan depressions (El-Gammal and Mehanna, 2003;Mehanna, 2004 andMehanna, 2005) in Lake Temsah (Mahomoud et al, 2011), in Nozha Hydrodrome (Mahmoud et al, 2013) and in Edku Lake (Khalil, 1994 andAbd-Alla &Talaat, 2000) and in El-Bahr El-Faroany (El-Kasheif et al, 2015). Table (7) shows different results from the previous studies, moreover, these differences in results may be due to feeding intensity, climate, gonad maturation and other factors.…”
Section: Discussionmentioning
confidence: 99%
“…M was estimated as 0.2 yr −1 and F as 0.9 yr −1 . E value was 0.82 (Mehanna 2004). According to Mahomoud et al (2011), the calculated Z was 2.656 for males and 1.88 for females of T. zilli in Lake Timsah.…”
Section: Discussionmentioning
confidence: 96%
“…The relative yield-per-recruit (Y/R) and relative biomass-per-recruit (B/R) of T. zilli in Wadi El-Raiyan lakes, Egypt, yielded E as 0.59 (Mehanna 2004). The current exploitation level of T. zillii in Lake Timah, Egypt, was E = 0.62 for males and 0.51 for females (Mahomoud et al 2011).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation